Preparation of magnetic Co0.5Zn0.5Fe2O4/AgBr hybrids for the visible-light-driven degradation of methyl orange. (January 2018) - Lin, Cuiping; Wang, Haodi; Liu, Shijia; Li, Chen; Chu, Binbin; Yan, Qishe
Abstract: Co0.5 Zn0.5 Fe2 O4 /AgBr hybrids with p-n heterojunction were prepared by a facile sol-gel and hydrothermal method. And the samples with different AgBr contents were characterized by XRD, 1 SEM, 2 UV–vis DRS 3 and FT-IR. 4 The degradation capability of the photocatalysts were evaluated under visible light and used methyl orange (MO) as a target contaminant. All the composites possessed the magnetic properties of Co0.5 Zn0.5 Fe2 O4 and also exhibited high photocatalytic activity of AgBr. Among the prepared photocatalysts, the hybrids prepared with 0.5 g AgNO3 exhibited the highest photocatalytic efficiency. The increase photocatalytic activity of Co0.5 Zn0.5 Fe2 O4 /AgBr hybrids might be associated with the formation of suitable internal structures between Co0.5 Zn0.5 Fe2 O4 and AgBr. And a possible photocatalytic mechanism of the Co0.5 Zn0.5 Fe2 O4 /AgBr hybrids was proposed.